PELANGGARAN TERHADAP HAK CIPTA TERKAIT LAGU “BINTANG” YANG DINYANYIKAN ULANG OLEH TINA TOON TANPA PERSETUJUAN PENCIPTA ASLI - Thalia Frederica; Gunardi Lie; Moody Rizqy Syailendra P. (PROSIDING SERINA, 2021)
Law is the foundation of social life in Indonesia. As a state of law, all activities that are carried out must be based on law, as well as intellectual property must be protected in accordance with the law. Copyright is one of intellectual property with the largest scope. With the law on copyright, all types of copying and piracy must be carried out in accordance with applicable legal provisions and with the permission of the copyright holder. Copyright infringement can be categorized as a criminal act and in the event of a violation, the infringing party must follow the applicable legal procedures and the sanctions that have been set. Indonesia itself is one of the countries where the number of copyright infringement is quite severe. These violations can be caused by a lack of public knowledge, economic factors, public attitudes, technological advances, low purchasing power, or lack of legal action. Like the case that ensnared Tina Toon and related parties. He sang again a single entitled "Star" which was previously popularized by the band Anima. However, this actually made him trapped in a copyright infringement case reported by Engkan Herikan, the owner of the song's copyright. In this study the author will use a qualitative research method with a descriptive approach. Researchers obtained data from observations of news texts published on various online news sites such as Kompas.com, Detiknews.com, and other supporting journals.